IMPLEMENTATION OF MERDEKA BELAJAR IN REALIZING SUSTAINABLE DEVELOPMENT GOALS FOR QUALITY EDUCATION IN PUBLIC ELEMENTARY SCHOOLS - Siregar, Laksamana Putra; Subhilhar, Subhilhar; Kusmanto, Heri; Ridho, Hatta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Advances in information, communication and transportation technology have accelerated globalization, creating a borderless world and fierce competition called “Hypercompetition” in the era of VUCA (volatility, uncertainty, complexity, ambiguity). Under these conditions, improving the quality of Human Resources (HR) through education becomes crucial. Education is one of the 17 goals in the Sustainable Development Goals (SDGs) launched by the United Nations in 2015, aiming to ensure quality and inclusive education for everyone. The “Merdeka Belajar” curriculum comes as an innovative response to this challenge. This research uses descriptive qualitative research methods. Data collection techniques used in-depth interviews, structured questionnaires and Focus Group Discussions (FGDs) with various stakeholders. Data analysis techniques involve transcription, reduction, classification, validation through triangulation and member checking, interpretation, and conclusion of research results. This research shows that the implementation of “Merdeka Belajar” in Medan City primary schools has great potential to realize the SDGs goals related to quality education. Despite facing challenges such as limited resources and digital infrastructure readiness, strategies such as continuous training, school collaboration with parents, and innovative policies have been implemented to support the successful implementation of this policy.